Leadership Model Analysis of the DPRD Chairman for the 2019-2024 Period in the Perspective of Political Resilience in Ciamis Regency - Setiawan, Sendi; Ida Parida; Moch. Rizal Arifin; Asep Abdul Rohman; Regi Refian Garis (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Basically, every person is born as a leader on this earth. Being a leader certainly comes with its own leadership model, tailored to one's personality. A leader undoubtedly has a significant impact on the progress of their subordinates and organization. The Regional Representative Council (DPRD) is an institution with a dual role: as a representative of the people and as an element of regional government administration. The DPRD institution must have a leader to manage the organization and ensure it operates according to the prevailing regulations. In managing the DPRD, a leader with a transformational leadership model brings a significant impact to the organization's journey. This study examines the analysis of the leadership model of the DPRD Chairman for the 2019-2024 period from the perspective of political resilience in Ciamis Regency. The study uses a descriptive qualitative method, exploring the analysis of the DPRD Chairman's leadership model for the 2019-2024 period in detail. The findings of the study analyze the leadership model, public aspirations, and the role of the DPRD Chairman in maintaining political resilience in Ciamis Regency. The conclusion of the study is that a transformational leader must be accountable for their actions and ensure stability within the organization. They must optimize human and organizational resources to achieve goals in line with their vision and mission. The process of cultivating public aspirations involves expressing interests in various activities and collaborating with the local community. This is crucial for maintaining political stability in Ciamis Regency